RETRACTED: The Influence of Interpersonal Communication, Work Motivation And Career Development on The Performance of Employees of Ramen Ya Jakarta Restaurant - Tri Widia Soleha; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science, 2024)
this research to analyze the effect of Interpersonal Communication, Work Motivation and Career Development on the Performance of YA Ramen Restaurant Employees. The research data used primary data in the form of a questionnaire to 105 employees of the YA Ramen Restaurant. The analytical method in this study used descriptive and inferential analysis with multiple linear regression and used the SPSS version 25 program. The technical data testing used in this study included multiple linear regression tests and hypothesis testing. The results of the research analysis found that Interpersonal Communication (X1), Work Motivation (X2), and Career Development (X3) have a positive and significant effect on Employee Performance (Y). The results of this study are expected to be able to make YA Ramen restaurant employees pay attention to Interpersonal Communication, Work Motivation, and Career Development which can improve Employee Performance.